Hashimoto’s thyroiditis presenting as cerebellar stroke - Manappallil, Robin George (Asian Journal of Medical Sciences, 2016)
Hashimoto’s thyroiditis (HT) or autoimmune hypothyroidism is the most common form of primary hypothyroidism, characterized by lymphocytic infiltration of the thyroid gland thereby leading to its destruction. It is more common in females. Genetic factors and chronic exposure to high iodine diet also play an important role. Hypertension, in these patients, is the result of increased peripheral resistance and arterial stiffness. The patient being reported is a 54 year old female with uncontrolled hypertension who presented with cerebellar infarct and was diagnosed to have HT. Following therapy with levothyroxine, her blood pressure was well controlled. This case emphasises the need for thyroid evaluation in all patients with uncontrolled hypertension. Asian Journal of Medical Sciences Vol.7(4) 2016 101-103